Long-term shoreline shifts on continental blocks during the Bajocian: an updated interpretation based on synthetic stratigraphical and palaeogeographical developments on regional scales - Ruban, Dmitry A.; Sallam, Emad S. (Geologos, 2019)
Available reconstructions of Jurassic global sea level changes differ and are in need of an update. New stratigraphical charts and palaeogeographical developments for a number of large continental blocks or their portions of these (e.g., Germany, India, northeast Africa, northwest Australia, the Russian Platform and western Siberia) reveal regional long-term shoreline shifts (i.e., transgressions and regressions) during the Bajocian Stage (168.3–170.3 Ma). A comparison of these allows to document only a single coherent feature, namely the earliest Bajocian transgression, in the majority of the continental blocks considered. Undoubtedly, this event was triggered by a eustatic rise. However, long-term shoreline shifts were either weak to absent or differed between the blocks during almost the entire Bajocian, thus providing evidence of the apparent stability of global sea level and the importance of regional tectonic activity as a control mechanism on particular transgressions and regressions. Interestingly, it appears that the earliest Bajocian eustatic rise was a constituent of a long-term eustatic pattern; the nature of this event has yet to be fully understood. Generally, the findings presented here are in better agreement with Anthony Hallam’s view of Jurassic eustasy and question some other global sea level reconstructions.